Tata Kelola Wisata Kuliner Sarapan Pagi dalam Pemberdayaan Usaha Mikro Kecil dan Menengah (UMKM) di Desa Punden Rejo, Tanjung Morawa (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2025)
This research aims to analyze the governance forms implemented by the village government in the breakfast culinary tourism program to empower Micro, Small, and Medium Enterprises (MSMEs) in Punden Rejo Village, Tanjung Morawa District, Deli Serdang Regency. It explores the application of good governance principles in local economic development based on culinary tourism. Using a descriptive qualitative approach, the study collected data through in-depth interviews, observations, and documentation from village officials, MSME actors, and tourists. The study is guided by Sedarmayanti's principles of good governance, particularly participation and accountability, linked to MSME empowerment. The results reveal that the breakfast culinary tourism management has not been optimal. Accountability is weak, as the village government has not registered or mentored MSMEs in the tourism sector to obtain a Business Identification Number (NIB) from the local Cooperative and MSME Office. Additionally, there is a lack of reporting on tax deductions and minimal support for business capital and training, causing many MSMEs to cease operations. From a participatory perspective, the village government has not actively involved community institutions like Pokdarwis, PKK, and Karang Taruna in planning and implementing activities, resulting in weak social support for MSMEs. Overall, the management of breakfast culinary tourism in Punden Rejo Village has not optimally empowered MSMEs due to weak implementation of accountability and participation principles. The success of sustainable tourism depends on cooperation between the village government, MSMEs, and local institutions to build a participatory and accountable tourism management system.